DESIGN, DEVELOPMENT AND CHARACTERIZATION OF CLOPIDOGREL BISULFATE TRANSDERMAL DRUG DELIVERY SYSTEM - REDDY P, DWARAKANADHA; SWARNALATHA D; SIDDA RAMANJULU B; KARTHIK SAI KUMAR P; SARDAR USSAIN M (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â Transdermal drug delivery is an alternative route for systemic drug delivery, which minimizes the absorption and increase the bioavailability. Orally clopidogrel bisulfate has a short elimination half-life (7-8 hrs), low oral bioavailability (50%) undergoes extensive first pass metabolism (85%) and frequent high doses (75 mg) are required to maintain the therapeutic level as a result, dose development toxic effect. The purpose of this research work was to formulation and evaluation of transdermal drug delivery system of clopidogrel bisulfate using various polymers such as sodium carboxymethylcellulose (SCMC), guar gum and tragacanth with different proportions by solvent evaporation technique. The Fourier transform infrared study revealed no physical or chemical interactions between clopidogrel bisulfate and excipients. Partition co-efficient present in between 2 and 6 for this drug so it is suitable for the transdermal patches. The prepared formulations were evaluated for different physicochemical characteristics such as thickness, folding endurance, drug content, percentage moisture absorption, percentage moisture loss, percentage elongation break test and weight uniformity. The diffusion studies were performed by using modified Franz diffusion cells. The result of dissolution studies shows that formulation, F6 (SCMC and tragacanth) showed maximum release of 98.6% in 24 hrs, whereas F1 (SCMC and guar gum) showed minimum release of 42.9% in 24 hrs. Based on the drug release and physicochemical values obtained the formulation F6 is considered as an optimized formulation, which shows higher percentage of drug release of 98.6% in 24 hrs. The developed transdermal patches increase the therapeutic efficacy and reduced toxic effect of clopidogrel bisulfate. Keywords: Clopidogrel bisulfate, Transdermal patch, Solvent casting techniques.